Juridic Review of Criminal Actions of Sexual Violence Against Women (Case Study in the Women and Children Service Unit of the Tangerang Police) - Nova Evriyana; Rokilah Rokilah (Nurani Hukum, 2021)
Violence against women in recent years has increased. Violence occurs anywhere, anytime and to anyone. Sexual violence against women often occurs because of the value system that places women as weak and inferior beings compared to men. Likewise with the view that the female body is a medium or a tool to satisfy male lust. With the large number of sexual violence that occurred, the Women and Children Service Unit of the Tangerang Police tried to resolve all cases without any case arrears. This study aims to determine the handling of cases of Sexual Violence Against Women in the Women and Children Service Unit of the Tangerang Police. To find out the obstacles in the process of handling Sexual Violence Against Women in the Women and Children Service Unit of the Tangerang Police. Researchers use the Juridical Empirical method which is also called field research. That is the main source of data obtained from the field. The results of the study revealed that the Women and Children Service Unit had carried out the handling in accordance with Articles 20 and 21 of the Regulation of the National Police Chief Number. 14 of 2012 concerning Management of Criminal Investigations.